Attitudes towards climate change aid and climate refugees in New Zealand: an exploration of policy support and ideological barriers. Issue 7 (10th November 2021) - Stanley, Samantha K.; Williamson, Jessica
ABSTRACT: Some individuals may be internationally displaced by climate change. We surveyed two independent samples of New Zealanders to understand attitudes towards climate aid. Participants were relatively less supportive of financial aid policies, though the majority supported climate refugee policy. We assessed whether those ideological barriers commonly used to predict prejudice and policy support related to this acceptance in meaningful ways. Interestingly, we show that approval or rejection of climate refugee policy was largely predicated on views regarding how hierarchically society ought to be ordered. Our research suggests that those opposing climate refugee policy are motivated by anti-egalitarianism and concerns about their own economic welfare to a greater extent than concerns about differences in culture, values, and norms.